Coated cutting tool and method for preparing the same
The AlxTi1-xCyN1-y coating was deposited through the CVD process, and the content of Al and Ti and the optimal grain orientation were adjusted to form a multi-period coating, which solved the problem of insufficient wear and peel resistance of TiAlN coating under high temperature conditions, achieved high wear resistance, peel resistance and high temperature oxidation resistance, and significantly improved cutting performance.
Patent Information
- Application Number
- CN202211049735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-08-30
AI Technical Summary
In the prior art, TiAlN coating has problems with insufficient wear and peeling resistance under high temperature conditions, which affects its performance in cutting processing.
The AlxTi1-xCyN1-y coating was deposited by CVD process. By adjusting the content of Al and Ti and the optimal grain orientation, a multi-period coating formed alternately with Ti-rich layer and Al-rich layer was formed to optimize the texture orientation and interlayer microstructure of the coating.
The coating has high wear resistance, peeling resistance and high temperature oxidation resistance, which significantly improves the cutting performance of cutting tools in turning, milling or drilling.
Smart Images

Figure CN115351317B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coated cutting tools, and particularly relates to a coated cutting tool and a preparation method thereof. Background Art
[0002] Today, with high-speed and dry cutting becoming the mainstream, the rapid development of coating technology plays a key role in improving tool performance and advancing cutting processing technology. Coated cutting tools have become an important symbol of modern tools.
[0003] TiAlN coatings have excellent properties such as high hardness, high oxidation temperature, good hot hardness, strong adhesion, low friction coefficient, and low thermal conductivity, and have been widely used in the high-performance cutting field of difficult-to-machine materials. Since Al atoms have good chemical affinity with O atoms, a very thin amorphous A12O3 layer will be formed in the tool-chip contact area under high-temperature action, thus forming a hard inert protective film. Therefore, TiAlN-coated tools can still maintain their excellent anti-wear performance even under high-temperature conditions.
[0004] Patent document WO2007003648A discloses a single-phase Ti 1- x Al x N (stoichiometric coefficient 0.75 < x ≤ 0.93) coating and its preparation method, using a Ti 1-x Al x N hard material layer generated by CVD without plasma excitation, existing as a single-phase layer with a cubic NaCl structure or where the Ti 1-x Al x N hard material layer is a multi-phase layer, the main phase of which is composed of Ti 1-x Al x N, containing wurtzite-structured Ti 1-x Al x N and / or TiNx with a NaCl structure as additional phases, which reacts in a reactor at a temperature of 700°C - 900°C and a pressure of 10 2 -10 5 Pa with titanium halide, aluminum halide, and NH3 and / or N2H4 as reactive nitrogen compounds to produce a Ti 1-x Al x N coating.
[0005] Patent document WO2009050110A discloses a connection layer-phase gradient layer-single-phase or multi-phase Ti 1-x Al xThe multi-layer coating is composed of a TiN / h-AlN layer. In the phase gradient layer, the connecting layer is composed of a TiN / h-AlN mixture. 1-x Al x In the N layer, fcc-TiAlN increases with the increase of layer thickness, and the increase is more than 50%. Meanwhile, TiN / h-AlN decreases with the increase of layer thickness.
[0006] In the above patent documents, the CVD-Ti 1-x Al x The N coating contains a high content of hexagonal AlN or amorphous carbon phases. Since the hardness of hexagonal AlN or amorphous carbon is significantly lower than that of fcc-TiAlN, it has a great adverse effect on the hardness and wear resistance of the coating.
[0007] It has been found that among PVD and CVD coatings, coatings with specific grain orientations show different characteristics and excellent performance for different processing conditions. Coatings with specific grain orientations have attracted great interest and attention from coating researchers.
[0008] WO2016148056A discloses a CVD-Ti 1-x Al x C y N 1-y Coating and preparation method thereof, and limited to the upper layer fcc-Ti 1-x Al x C y N 1-y Ti and Al in the middle change periodically, and I(200) / I(111)>10; lower layer: fcc-Ti 1-x Al x C y N 1-y There is no periodic change in Ti and Al, and I(200) / I(111) < 3. However, with the deepening of research, different methods can be adopted to obtain different growth texture orientations for different coating materials. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a coated cutting tool having excellent wear resistance, coating anti-peeling performance and high-temperature oxidation resistance and a preparation method thereof, which has better cutting performance in turning, milling or drilling.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0011] A coated cutting tool comprises a tool substrate and a wear-resistant coating arranged on the tool substrate, wherein the wear-resistant coating comprises at least Alx Ti 1-x C y N 1-y The coating, wherein 0.35≤x≤0.98, 0.35≤x+y≤1.05, the Al x Ti 1- x C y N 1-y The coating has a preferred texture orientation relative to the crystal {111} and {311} planes. x Ti 1-x C y N 1-y The texture coefficient of the coating satisfies: 0.8≤TC(111)≤6.0, 0.8≤TC(311)≤6.0, and 3.5≤TC(111)+TC(311)≤6.0.
[0012] TC(hkl) is defined as follows:
[0013]
[0014] in,
[0015] I(hkl) = measured intensity of (hkl) reflection;
[0016] I0(hkl) = standard intensity of the (311) reflection according to the standard powder diffraction data of the applied JCPDF card No. 00-46-1200;
[0017] I(hkl) i =(hkl) i The measured intensity of the reflection;
[0018] I0(hkl) i = (hkl) according to the standard powder diffraction data of JCPDF card No. 00-46-1200 applied i Standard intensity of reflection;
[0019] n = the number of reflections used in the calculation, n = 6;
[0020] (hkl) i Used (hkl) i The reflective crystal planes are: (111), (200), (220), (311), (331) and (420).
[0021] The above-mentioned coated cutting tool, preferably, the Al x Ti 1-x C y N 1-yThe microstructure of the coating is a fibrous columnar structure. x Ti 1-x C y N 1-y The average width of columnar grains at 90% thickness in the coating growth direction is d, Al x Ti 1-x C y N 1-y The thickness of the coating is h, and the ratio of h to d is h / d≥8.
[0022] The above-mentioned coated cutting tool, preferably, the Al x Ti 1-x C y N 1-y Any section in the coating perpendicular to the surface of the tool substrate, along the Al x Ti 1-x C y N 1-y In the growth direction of the coating, it is composed of alternating Ti-rich layers and Al-rich layers, and there is a periodic concentration change of alternating Ti and Al. The Al atomic fraction in the Ti-rich layer is lower than that in the Al-rich layer, and the Ti atomic fraction in the Ti-rich layer is higher than that in the Al-rich layer, and the highest peak position of the Al atomic fraction corresponds to the lowest peak position of the Ti atomic fraction.
[0023] The above-mentioned coated cutting tool, preferably, the Al x Ti 1-x C y N 1-y Any section in the coating perpendicular to the surface of the tool substrate, along the Al x Ti 1-x C y N 1-y In the coating growth direction, the area on the Al element distribution curve that is higher than the average atomic fraction of Al element in the coating is the periodic width d of the Al-rich layer. Al The area on the Al element distribution curve that is lower than the average atomic fraction of Al element in the coating is the periodic width d of the Ti-rich layer. Ti , then 0.1≤d Al / d Ti ≤50, and 0.1nm≤d Al ≤100nm.
[0024] In the above-mentioned coated cutting tool, preferably, the Ti-rich layer and the Al-rich layer are both face-centered cubic (fcc) crystal structures.
[0025] The above-mentioned coated cutting tool, preferably, the Al x Ti 1-x Cy N 1-y The nanohardness of the coating is greater than 32 GPa.
[0026] In the above-mentioned coated cutting tool, preferably, the wear-resistant coating also includes a x Ti 1- x C y N 1-y A hard base layer between the coating layers has a thickness of 0.1 μm to 8 μm and is selected from one of a CVD deposited TiN layer, a TiCN layer and an h-AlN layer or a combination thereof.
[0027] In the above-mentioned coated cutting tool, preferably, the wear-resistant coating further comprises a x Ti 1-x C y N 1-y A hard surface layer on the coating, wherein the thickness of the hard surface layer is greater than 0.1 μm, and the hard surface layer is selected from one of a CVD deposited TiN layer, a TiC layer, a TiCN layer and an AlN layer or a combination thereof.
[0028] For the above-mentioned coated cutting tool, preferably, the total thickness of the wear-resistant coating is 2 μm to 25 μm.
[0029] In the above-mentioned coated cutting tool, preferably, the tool substrate comprises a tool substrate made of cemented carbide, ceramic, steel or cubic boron nitride.
[0030] As a general technical concept, the present invention also provides a method for preparing the above-mentioned coated cutting tool, comprising the following steps:
[0031] The Al2O3 is deposited on the tool substrate by CVD process (preferably low pressure CVD process). x Ti 1-x C y N 1-yThe coating process comprises: introducing the reaction gas into the coating furnace through two gas pipelines, wherein the gas mixture V1 in the first gas pipeline contains 0.002 volume % to 1.1 volume % of TiCl4, 0.025 volume % to 2.7 volume % of AlCl3 and 0 to 0.8 volume % of a carbon source, and the remainder is a first carrier gas, wherein the carbon source is selected from one or more of acetonitrile, ethane, ethylene and acetylene, and the carrier gas is a mixture of hydrogen and nitrogen or hydrogen; the gas mixture V2 in the second gas pipeline contains 0.02 volume % to 15 volume % of a nitrogen source , the balance is a second carrier gas, the nitrogen source is selected from at least one of NH3 and N2H4, the second carrier gas is a mixture of hydrogen and nitrogen or is hydrogen; the volume ratio of the gas mixture V1 to V2 is 1 to 13:1, the two gases are kept separate and mixed before entering the preheater of the coating furnace, and then deposited in the CVD reactor through an open graphite rod connected to the preheater, the rotation speed of the preheater and the graphite rod is 0.5rpm to 30rpm, the deposition temperature is controlled at 650℃ to 910℃, and the deposition pressure is controlled at 1mbar to 10mbar.
[0032] The method for preparing the coated cutting tool is preferably performed by depositing Al x Ti 1-x C y N 1-y Prior to coating, a hard base layer is deposited on the tool substrate.
[0033] The method for preparing the coated cutting tool is preferably performed by depositing Al x Ti 1-x C y N 1-y After coating, it also includes Al x Ti 1-x C y N 1-y A hard surface layer is deposited on the coating.
[0034] The method for preparing the coated cutting tool mentioned above preferably further comprises surface wet sandblasting and / or polishing after obtaining the coated cutting tool.
[0035] Surprisingly, it was found that in a further preferred embodiment of the present invention, Al x Ti 1-x C y N 1-y The coating has a nanohardness (HV) greater than 32 GPa, or even greater than 33 GPa. The coating has a low hardness and low wear resistance. x Ti 1-x C y N 1-yHigh hardness of the coating.
[0036] The cutting tool of the present invention may also be subjected to surface wet sandblasting and / or polishing treatment to obtain better blade surface quality and processing performance.
[0037] In addition, the hard surface layer in the present invention can be x Ti 1-x C y N 1-y The hard surface layer and the hard base layer are used at the same time, so that more excellent performance can be obtained. At the same time, the hard surface layer in the present invention can also be used as a surface coloring layer to obtain better appearance and use recognition.
[0038] Surprisingly, it has been found that the method of the present invention makes it possible to apply one or more wear-resistant coatings on a substrate made of a superhard material such as cemented carbide, cermet, ceramic, steel or cubic boron nitride, which has a total thickness of 2 μm to 25 μm and includes at least Al prepared by chemical vapor deposition (CVD). x Ti 1-x C y N 1-y Coating, where 0.35≤x≤0.98, 0.35≤x+y≤1.05. Measured using Cuka radiation, Al x Ti 1-x C y N 1-y The layer exhibits an X-ray diffraction pattern and has a preferred crystal growth orientation, Al x Ti 1-x C y N 1-y The layer texture coefficient is 3.5≤(TC(111)+TC(311))≤6.0, and 0.8≤TC(111)≤6.0, 0.8≤TC(311)≤6.0. The cutting tool of the present invention has excellent wear resistance, chipping resistance and high temperature oxidation resistance, and has extremely excellent performance in the field of processing difficult-to-process materials such as cast iron, stainless steel, alloy steel, cast steel, and high temperature alloy.
[0039] The coating of the present invention can be used on steel tools, hard material (including hard alloy, metal ceramic and ceramic, etc.) substrates.
[0040] Compared with the prior art, the advantages of the present invention are:
[0041] 1. Aiming at the problem of Al content limitation in TiAlN coating, the present invention adopts ultra-low pressure CVD (LPCVD) process to deposit Al x Ti 1-x C y N 1-yThe atmosphere of the coating deposition system was differentially controlled to achieve the deposition of high Al content on the cutting tool surface with a preferred crystal growth orientation and an Al content of 3.5≤(TC(111)+TC(311))≤6.0. x Ti 1-x C y N 1-y coating.
[0042] 2. Al of the present invention x Ti 1-x C y N 1-y The coating is a multi-periodic coating of a nanostructure composed of a Ti-rich layer and an Al-rich layer as a modulated period, and an optimized structure of the Ti-rich layer and the Al-rich layer is achieved through differentiated control of the deposition process.
[0043] 3. Al of the present invention x Ti 1-x C y N 1-y The coating achieves the optimization and regulation of the interlayer structure of the wear-resistant coating by controlling the texture orientation and interlayer microstructure. x Ti 1-x C y N 1-y The coating particles are small in width and have a slender fibrous columnar crystal structure. The coating nanohardness is as high as 32GP or more, showing excellent wear resistance.
[0044] 4. The coated cutting tool of the present invention has excellent wear resistance, coating anti-stripping performance and high-temperature oxidation resistance, and has extremely excellent performance in the processing fields of cast iron, stainless steel, alloy steel, cast steel, high-temperature alloy and other materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Schematic diagram of the structure of the coated cutting tool A3 in Example 1 of the present invention.
[0046] Figure 2 is the Al of the coated cutting tool A1 in Example 1 of the present invention x Ti 1-x C y N 1-y SEM image of the fracture cross-section of the coating.
[0047] Figure 3 is the Al of the coated cutting tool A1 in Example 1 of the present invention x Ti 1-x C y N 1-yy Periodic multilayer TEM morphology of the coating (STEM-HAADF-DF).
[0048] Figure 4 is the Al of the coated cutting tool A1 in Example 1 of the present invention x Ti 1-x C y N 1-y Energy spectrum line scanning analysis diagram of the layered structure area in the coating.
[0049] Legend:
[0050] 1. Tool base; 2. Wear-resistant coating; 3. Hard base layer; 4. Al x Ti 1-x C y N 1-y coating; 5. hard surface layer; 6. Al-rich layer; 7. Ti-rich layer. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.
[0052] Example 1
[0053] A coated cutting tool according to the present invention, such as Figure 1 As shown, the tool substrate 1 is made of cemented carbide material and a wear-resistant coating 2 coated thereon, wherein the wear-resistant coating 2 has a total thickness of 2 μm to 25 μm and includes at least Al prepared by chemical vapor deposition (CVD) method. x Ti 1-x C y N 1-y Coating 4, where 0.35≤x≤0.98, 0.35≤x+y≤1.05. Measured using Cuka radiation, Al x Ti 1-x C y N 1-y The layer exhibits an X-ray diffraction pattern with a preferred texture orientation relative to the crystal {111} and {311} planes. x Ti 1-x C y N 1-y The texture coefficient of coating 4 satisfies: 0.8≤TC(111)≤6.0, 0.8≤TC(311)≤6.0, and 3.5≤TC(111)+TC(311)≤6.0.
[0054] TC(hkl) is defined as follows:
[0055]
[0056] in,
[0057] I(hkl) = measured intensity of (hkl) reflection;
[0058] I0(hkl) = standard intensity of the (311) reflection according to the standard powder diffraction data of the applied JCPDF card No. 00-46-1200;
[0059] I(hkl) i =(hkl) i The measured intensity of the reflection;
[0060] I0(hkl) i = (hkl) according to the standard powder diffraction data of JCPDF card No. 00-46-1200 applied i Standard intensity of reflection;
[0061] n = the number of reflections used in the calculation, n = 6;
[0062] (hkl) i Used (hkl) i The reflective crystal planes are: (111), (200), (220), (311), (331) and (420).
[0063] In this embodiment, Al x Ti 1-x C y N 1-y The microstructure of coating 4 is a fibrous columnar structure. x Ti 1-x C y N 1-y The average width of the columnar grains at 90% thickness in the growth direction of coating 4 is d, Al x Ti 1-x C y N 1-y The thickness of the coating 4 is h, and the ratio of h to d is h / d≥8.
[0064] In this embodiment, Al x Ti 1-x C y N 1-y Any section in the coating 4 perpendicular to the surface of the tool substrate 1, along the Al x Ti 1-x C y N 1-yIn the growth direction of the coating 4, it is composed of alternating Ti-rich layers 7 and Al-rich layers 6, and there is a periodic concentration change of alternating Ti and Al. The Al atomic fraction in the Ti-rich layer 7 is lower than the Al atomic fraction in the Al-rich layer 6, and the Ti atomic fraction in the Ti-rich layer 7 is higher than the Ti atomic fraction in the Al-rich layer 6, and the highest peak position of the Al atomic fraction corresponds to the lowest peak position of the Ti atomic fraction.
[0065] In this embodiment, Al x Ti 1-x C y N 1-y The coating 4 is a multi-periodic coating composed of an Al-rich layer 6 and a Ti-rich layer 7 as a modulation period. x Ti 1-x C y N 1-y In the growth direction of coating 4, the area on the Al element distribution curve that is higher than the average atomic fraction of Al element in the coating is the period width d of Al-rich layer 6. Al The area on the Al element distribution curve that is lower than the average atomic fraction of Al element in the coating is the period width d of the Ti-rich layer 7. Ti , then 0.1≤d Al / d Ti ≤50, and 0.1nm≤d Al ≤100nm.
[0066] In this embodiment, both the Ti-rich layer 7 and the Al-rich layer 6 have a face-centered cubic (fcc) crystal structure.
[0067] In this embodiment, Al x Ti 1-x C y N 1-y The nanohardness of coating 4 is greater than 32 GPa.
[0068] In this embodiment, the tool substrate 1 and the Al x Ti 1-x C y N 1-y A hard base layer 3 is also included between the coating layers 4. The thickness of the hard base layer 3 is 1.0 μm. The hard base layer 3 is a TiN layer deposited by CVD.
[0069] In this embodiment, Al x Ti 1-x C y N 1-y The coating 4 may further include a hard surface layer 5 deposited by CVD. The thickness of the hard surface layer 5 is greater than 0.1 μm. The hard surface layer 5 is selected from one of the TiN layer, TiC layer, TiCN layer, and AlN layer deposited by CVD, or a combination thereof.
[0070] In this embodiment, the tool substrate 1 can also be made of ceramic (metal ceramic or non-metal ceramic), steel or cubic boron nitride.
[0071] A method for preparing the coated cutting tool of this embodiment comprises the following steps:
[0072] (1) A mixed powder with a Co content (mass fraction) of 8%, a TaNbC content of 0.5%, and a WC Fisher particle size of 3.3 μm was pressed, sintered, and ground to produce a WC-Co cemented carbide substrate with a blade shape specified by ISO standard SEET12T3-CM. To prepare an indexable coated cutting blade, coating was performed in a CVD coating furnace equipped with a low pressure system (LPS). The gas flow was radial relative to the longitudinal axis of the reactor. A hard base layer 3TiN was deposited on the tool substrate 1 using an existing CVD process with a deposition thickness of 1.0 μm.
[0073] (2) Deposition of Al x Ti 1-x C y N 1-y Coating 4: Al is deposited on the hard base layer 3TiN layer x Ti 1-x C y N 1-y Coating 4, deposition parameters are shown in Table 1. The two gases V1 and V2 are kept separate and mixed before entering the preheater of the coating furnace, and then deposited in the CVD reactor through a hollow graphite rod with holes around it connected to the preheater. Al is deposited on the A1-A4 coated tools. x Ti 1-x C y N 1-y The rotation speeds of the preheater and the graphite rod during coating 4 were 1 rpm, 1 rpm, 2 rpm, and 4 rpm, respectively. Al was deposited in a CVD reactor. x Ti 1-x C y N 1-y Coating 4.
[0074] (3) Deposition of hard surface layer 5: Al2O3 on tools A3 and A4 x Ti 1-x C y N 1-y A hard surface layer 5 is deposited on the surface of the coating 4. x Ti 1-x C y N 1-y The surface of coating 4 is deposited with a TiN layer using the existing CVD process, with a deposition thickness of 1.0 μm. x Ti1-x C y N 1-y An AlN layer is deposited on the surface of the coating 4 by using the existing low-pressure CVD process, and the deposition thickness is 0.5 μm.
[0075] Table 1A1 x Ti 1-x C y N 1-y Coating deposition process parameters
[0076]
[0077] Coating crystallization preferred orientation detection:
[0078] The X-ray diffraction (XRD) method was used to determine the preferred crystal orientation. Table 2 shows the texture orientation test results of the prepared coating blades.
[0079] Table 2A1 x Ti 1-x C y N 1-y Coating Orientation
[0080]
[0081] Coating composition and grain size detection:
[0082] The coating composition was analyzed by SEM-EDS, as shown in Table 3; the Ti 1-x Al x C y N 1-y The cross section of the coating was obtained by cutting with a diamond saw blade along the direction perpendicular to the upper and lower surfaces of the blade. After mounting, grinding and polishing, the thickness of each layer of the coating was determined by SEM, as shown in Table 3. x Ti 1-x C y N 1-y The average width of the columnar crystal grains measured at 90% of the thickness of the layer is d, and then the ratio h / d is calculated based on the coating thickness value h in Table 1. The results are shown in Table 3.
[0083] Table 3A1 x Ti 1-x C y N 1-y Coating composition (at.%) and structure
[0084]
[0085] Ti of the present invention 1-x Al xC y N 1-y The typical thickness of the layer is about 5 to 15 μm, and its thickness is highly correlated with the deposition time. 1-x Al x C y N 1-y The columnar crystals have an average width of 0.5 to 1.5 μm and an aspect ratio of about 8 to 15, measured at 90% of the thickness of the layer.
[0086] Coating structure and morphology detection:
[0087] Figure 2 Ti of the tool A1 of the present invention 1-x Al x C y N 1-y The cross-sectional morphology of the coating fracture. Under the high-magnification photograph of its fracture morphology, the lamellar morphology at the crystal plane fracture can be observed. Figure 3 Ti of the tool A1 of the present invention 1-x Al x C y N 1-y In the STEM-HAADF-DF image of the coating, a "fishbone"-like flake structure can be observed in the bright area in the middle. Figure 3 The energy spectrum analysis data of the lamellar morphology of the region was used to draw the energy spectrum line scanning element content (intensity) distribution diagram, such as Figure 4 As shown. Figure 4 , along the Ti 1-x Al x C y N 1-y In the coating growth direction, the coating is composed of alternating Ti-rich layers 7 and Al-rich layers 6, and there is a periodic concentration change of Ti and Al alternating. According to the average Al atomic fraction in Table 3, the regions of Ti-rich layer 7 and Al-rich layer 6 can be determined in the energy spectrum line scanning element content distribution diagram. The Al atomic fraction in the Ti-rich layer 7 is lower than the Al atomic fraction in the Al-rich layer 6, the Ti atomic fraction in the Ti-rich layer 7 is higher than the Ti atomic fraction in the Al-rich layer 6, and the highest peak position of the Al atomic fraction corresponds to the lowest peak position of the Ti atomic fraction. According to Figure 4 , Al-rich layer 6 width period d Al The width of the Ti-rich layer is about 11 nm. Ti is about 6nm, d Al / d Ti =1.83. Using the same analysis and measurement method, the Ti of tool A2 is measured. 1- x Al x C y N1-y The width period of Al-rich layer 6 in the coating is d Al The width period of the Ti-rich layer is about 12 nm. Ti is about 6nm, d Al / d Ti =2; Ti of tool A3 1-x Al x C y N 1-y The width period of Al-rich layer 6 in the coating is d Al The width period of the Ti-rich layer 7 is about 10 nm. Ti is about 4 nm, d Al / d Ti =2.5; Ti of tool A4 1-x Al x C y N 1-y The width period of Al-rich layer 6 in the coating is d Al The width period of the Ti-rich layer 7 is about 15 nm. Ti is about 3nm, d Al / d Ti =5.
[0088] By EDS analysis it is possible to show that narrow areas showing dark platelets in BF and bright platelets in HAADF have a higher Ti proportion and a lower Al proportion than wider areas. However, in the various areas the proportion of nitrogen is of the same order of magnitude within the measurement accuracy. The overall composition determined by EDS is identical to that determined by XRD.
[0089] Coating nanohardness test:
[0090] The coated blades were polished and then subjected to nanohardness testing, as shown in Table 4.
[0091] Table 4A1 x Ti 1-x C y N 1-y Layer nanohardness test results
[0092] performance A1 A2 A3 A4 Hv / GPa 33.9±0.9 35.2±1.2 32.8±0.7 34.3±1.1
[0093] Example 2 Cutting Test
[0094] A comparative cutting test was conducted on the comparative coated cutting tools H1 and H2 respectively having the A1, A2, A3, A4 cutting tools of the present invention produced according to Example 1 and having the same cutting tool substrate 1 as Example 1. The comparative coated cutting tools are the H1 cutting tools coated by the existing CVD process: TiN / MT-TiCN / TiN (total thickness 10 μm) and the H2 cutting tools: TiN / MT-TiCN / Al2O3 (total thickness 15 μm).
[0095] The above cutting tools were subjected to milling tests as shown in Table 5, respectively.
[0096] Table 5 Milling experiment mode
[0097]
[0098] Table 6 Comparison of test results
[0099] product Milling life (min) <![CDATA[Wear V b (mm)]]> A1 (the present invention) 82 0.42 A2 (the present invention) 75 0.29 A3 (the present invention) 88 0.32 A4 (the present invention) 78 0.45 H1(Comparison tool) 42 0.64 H2(Comparison tool) 46 0.57
[0100] According to Table 6, the tool life of the coating of the present invention is significantly better than that of the comparative tool, showing excellent wear resistance.
[0101] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A coated cutting tool, characterized in that: It comprises a tool base and a wear-resistant coating arranged on the tool base, wherein the wear-resistant coating comprises at least Al x Ti 1-x C y N 1-y The coating, wherein 0.35≤x≤0.98, 0.35≤x+y≤1.05, the Al x Ti 1-x C y N 1-y The coating has a preferred texture orientation relative to the crystal {111} and {311} planes. x Ti 1- x C y N 1-y The texture coefficient of the coating satisfies: 2.7≤TC(111)≤6.0, 2.1≤TC(311)≤6.0, and 4.8≤TC(111)+TC(311)≤6.0; The Al x Ti 1-x C y N 1-y Any section in the coating perpendicular to the surface of the tool substrate, along the Al x Ti 1-x C y N 1-y In the growth direction of the coating, it is composed of alternating Ti-rich layers and Al-rich layers, and there is a periodic concentration change of Ti and Al alternating. The Al atomic fraction in the Ti-rich layer is lower than that in the Al-rich layer, and the Ti atomic fraction in the Ti-rich layer is higher than that in the Al-rich layer. The highest peak position of the Al atomic fraction corresponds to the lowest peak position of the Ti atomic fraction. The Al x Ti 1-x C y N 1-y Any section in the coating perpendicular to the surface of the tool substrate, along the Al x Ti 1-x C y N 1-y In the coating growth direction, the area on the Al element distribution curve that is higher than the average atomic fraction of Al element in the coating is the periodic width d of the Al-rich layer. Al The area on the Al element distribution curve that is lower than the average atomic fraction of Al element in the coating is the periodic width d of the Ti-rich layer. Ti , then 2≤d Al / d Ti ≤5, and 10nm≤d Al ≤15nm.
2. The coated cutting tool according to claim 1, characterized in that The Al x Ti 1-x C y N 1-y The microstructure of the coating is a fibrous columnar structure. x Ti 1-x C y N 1-y The average width of columnar grains at 90% thickness in the coating growth direction is d, Al x Ti 1-x C y N 1-y The thickness of the coating is h, and the ratio of h to d is h / d≥8.
3. The coated cutting tool according to claim 1, characterized in that The Ti-rich layer and the Al-rich layer both have a face-centered cubic (fcc) crystal structure.
4. The coated cutting tool according to any one of claims 1 to 3, characterized in that: The Al x Ti 1-x C y N 1-y The nanohardness of the coating is greater than 32 GPa.
5. The coated cutting tool according to any one of claims 1 to 3, characterized in that: The wear-resistant coating also includes a layer provided between the tool substrate and Al x Ti 1-x C y N 1-y A hard base layer between the coating layers has a thickness of 0.1 μm to 8 μm and is selected from one of a CVD deposited TiN layer, a TiCN layer and an h-AlN layer or a combination thereof.
6. The coated cutting tool according to any one of claims 1 to 3, characterized in that: The wear-resistant coating also includes a layer provided on the Al x Ti 1-x C y N 1-y A hard surface layer on the coating, wherein the thickness of the hard surface layer is greater than 0.1 μm, and the hard surface layer is selected from one of a CVD deposited TiN layer, a TiC layer, a TiCN layer and an AlN layer or a combination thereof.
7. The coated cutting tool according to any one of claims 1 to 3, characterized in that: The total thickness of the wear-resistant coating is 2 μm to 25 μm.
8. The coated cutting tool according to any one of claims 1 to 3, characterized in that: The tool matrix includes a tool matrix made of cemented carbide, ceramic, steel or cubic boron nitride.
9. A method for preparing a coated cutting tool according to any one of claims 1 to 8, characterized in that: The following steps are involved: Al is deposited on the tool substrate using CVD technology x Ti 1-x C y N 1-y The coating process comprises: introducing the reaction gas into the coating furnace through two gas pipelines, wherein the gas mixture V1 in the first gas pipeline contains 0.002 volume % to 1.1 volume % of TiCl4, 0.025 volume % to 2.7 volume % of AlCl3 and 0 to 0.8 volume % of a carbon source, and the remainder is a first carrier gas, wherein the carbon source is selected from one or more of acetonitrile, ethane, ethylene and acetylene, and the carrier gas is a mixture of hydrogen and nitrogen or hydrogen; the gas mixture V2 in the second gas pipeline contains 0.02 volume % to 15 % by volume of a nitrogen source, the remainder being a second carrier gas, the nitrogen source being selected from at least one of NH3 and N2H4, the second carrier gas being a mixture of hydrogen and nitrogen or being hydrogen; the volume ratio of the gas mixture V1 to V2 is 1 to 13:1, the two gases are kept separate and mixed before entering the preheater of the coating furnace, and then deposited in a CVD reactor through an open graphite rod connected to the preheater, the rotation speed of the preheater and the graphite rod is 0.5 rpm to 30 rpm, the deposition temperature is controlled at 650°C to 910°C, and the deposition pressure is controlled at 1 mbar to 10 mbar.
10. The method for preparing a coated cutting tool according to claim 9, characterized in that: In the deposition of Al x Ti 1-x C y N 1-y Prior to coating, a hard base layer is deposited on the tool substrate.
11. The method for preparing a coated cutting tool according to claim 9, characterized in that: In the deposition of Al x Ti 1-x C y N 1-y After coating, it also includes Al x Ti 1-x C y N 1-y A hard surface layer is deposited on the coating.
12. The method for preparing a coated cutting tool according to any one of claims 9 to 11, characterized in that: After obtaining the coated cutting tool, the surface is wet blasted and / or polished.
Citation Information
Patent Citations
Hard-coated body and method for production thereof
WO2007003648A1
Bodies coated with a hard material and method for the production thereof
WO2009050110A2
Surface-coated cutting tool with rigid coating layers exhibiting excellent chipping resistance
WO2016148056A1
Surface-coated cutting tool and method for producing same
CN107438491A
Coated cutting tool and preparation method thereof
CN111482622A